“Dak Kawa Nyusah” as Cultural Rationality: Reinterpretation of Local Values in Strengthening Community Social Cohesion in Pangkal Pinang City - Dede Irma Herlina; Wilodati; Siti Komariah (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Social transformation in multicultural societies often faces the potential for conflict and disintegration due to cultural diversity and the flow of globalization. However, in certain contexts, social change can actually act as an adaptive mechanism in strengthening social cohesion. This study aims to analyze the reinterpretation of the value of “dak kawa nyusah” as form of cultural rationality and its implications for social cohesion in Pangkal Pinang City. This study uses a qualitative approach with a case study method, through in-depth interviews, observation, and documentation. The results show that the value of “dak kawa nyusah” not only functions as a value that encourages tolerance and social harmony, but also as a cultural mechanism that implicitly regulates the boundaries of social interaction. The resulting social cohesion is open and stable, but not fully integrative, characterized by ambivalence between tolerance and the potential for disengagement. In this context, local values play a dual role: as social glue and as a mechanism that limits the dept of social relations. These findings confirm that social cohesion in multicultural societies is not static, but rather the result of a dynamic negotiation process between social structures, cultural values and daily practices.